Persepsi Pemustaka terhadap Koleksi Buku dengan Subjek Minangkabau di Pusat Dokumentasi dan Informasi Kebudayaan Minangkabau (PDIKM) Padang Panjang - Rafiqah, Dina; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
The purpose of writing this article for description about. First, librarian perception about relevance of Minangkabau collection. Second, librarian perception about completeness of Minangkabau collection. Third, librarian perception about latest of Minangkabau collection in Documentation Centre and Culture Information Minangkabau Padang Panjang. The method used is descriptive. Based on analysis of the discussion can be concluded three things. First, librarian about relevance Minangkabau collection because collection that available can give compliance required information for librarian. Second, librarian perception about completeness of Minangkabau collection viewed from provided information just some needs are met, but for another librarian yet to meet the needs of the information. Third, perception about latest of Minangkabau collection not update yet. Keywords: perception, collection, Minangkabau